Risk factors for dysphagia after anterior cervical spine surgery: A meta-analysis. Issue 10 (March 2017) - Liu, Feng-Yu; Yang, Da-Long; Huang, Wen-Zheng; Huo, Li-Shuang; Ma, Lei; Wang, Hui; Yang, Si-Dong; Ding, Wen-Yuan
Abstract: Background: Dysphagia is a well-known complication following anterior cervical spine surgery. Although risk factors for dysphagia have been reported in the literature, they still remain controversial. This study aims to investigate the risk factors associated with dysphagia following anterior cervical spinal surgery. Methods: PubMed, EMBASE, and The Cochrane Library were searched up to June 2016 for studies examining dysphagia following anterior cervical spinal surgery. Risk factors associated with dysphagia were extracted. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated for outcomes. Data analysis was conducted with RevMan 5.3 and STATA 12.0. Results: The final analysis includes a total of 18 distinct studies. The pooled analysis reveals that there are significant differences in female gender (OR = 2.30, 95% CI: 1.76–2.99, P  < 0.001), the use of anterior cervical plate (OR = 1.66, 95% CI: 1.05–2.62, P  = 0.03), more than 1 surgical level (OR = 2.07, 95% CI: 1.62–2.66, P  < 0.001), the upper surgical level at C3/4 (OR = 3.08, 95% CI: 1.44–6.55, P  = 0.004), and the use of bone morphogenetic protein-2 (rhBMP-2) (OR = 5.52, 95% CI: 2.16–14.10, P  < 0.001). However, no significant difference is found in revision surgery (OR = 1.67, 95% CI: 0.60–4.68, P  = 0.33), the type of fusion (OR = 1.02, 95% CI: 0.62–1.67, P  = 0.95), and cervical disc arthroplasty (OR = 1.37, 95% CI: 0.75–2.51, P  = 0.30). Conclusion: Female gender, the use of anterior cervical plate, more than 1 surgical level, the upper surgical level at C3/4, and the use of rhBMP-2 are the risk factors for dysphagia following anterior cervical spinal surgery. However, revision surgery, the type of fusion, and cervical disc arthroplasty are unassociated with dysphagia. Considering the limited number of studies, this conclusion should be interpreted cautiously, and larger scale studies are required.